Fuzzy control embedded in microcontroller and applied to an experimental apparatus using magnetorheological fluid damper - De Abreu, Gustavo Luiz C. M. [UNESP]; De Melo, Gilberto Pechoto [UNESP]; Lopes Jr., Vicente [UNESP] (Springer Nature, 2013)
This work focuses on applying fuzzy control embedded in microcontrollers in an experimental apparatus using magnetorheological fluid damper. The non-linear behavior of the magnetorheological dampers associated with the parametric variations on vehicle suspension models corroborate the use of the fuzzy controllers. The fundamental formulation of this controller is discussed and its performance is shown through numeric simulations. An experimental apparatus representing a two degree of freedom system containing a magnetorheological damper is used to identify the main parameters and to evaluate the performance of the closed-loop system with the embedded low-cost microcontroller-based fuzzy controller. © 2013 Brazilian Society for Automatics - SBA.
Keywords: Fuzzy logic; Magnetorheological damper; Microcontroller; Vibration control; Experimental apparatus; Magneto-rheological dampers; Magnetorheological fluid damper; Microcontroller-based; Nonlinear behavior; Numeric simulation; Parametric variation; Two-degree-of-freedom system; Fuzzy control; Magnetorheological fluids; Microcontrollers; Vehicle suspensions; Controllers